Menanamkan Kedisiplinan Melalui Shalat Berjamaah - Subkhan Muhammad (GHIROH, 2023)
The low level of discipline among students is a problem that can hinder the learning process. One of the efforts to instill discipline is through the habit of performing congregational prayers. The purpose of this study is to determine how to instill discipline among students through the habit of congregational prayers. The methodology used in this research is qualitative research. Several steps that can be taken to instill discipline through congregational prayers include: 1) Providing clear understanding; 2) Setting a good example; 3) Inviting students gently; 4) Scheduling congregational prayer times; 5) Providing praise and rewards; 6) Guidance and supervision; 7) Evaluation and improvement. In order for the efforts to instill discipline through congregational prayers to be effective, it is necessary to establish good habits both at home and at school. Establishing habits at school certainly requires a special schedule and optimal guidance from teachers and all school members.